Modelling the impacts of altered management practices, land use and climate changes on the water quality of the Millbrook catchment-reservoir system in South Australia. (1st November 2017) - Nguyen, Hong Hanh; Recknagel, Friedrich; Meyer, Wayne; Frizenschaf, Jacqueline; Shrestha, Manoj Kumar
Abstract: Sustainable management of drinking water reservoirs requires taking into account the potential effects of their catchments' development. This study is an attempt to estimate the daily patterns of nutrients transport in the catchment – reservoir systems through the application of the ensemble of complementary models SWAT-SALMO. SWAT quantifies flow, nitrate and phosphate loadings originating in catchments before entering downstream reservoirs meanwhile SALMO determines phosphate, nitrate, and chlorophyll-a concentrations within the reservoirs. The study applies to the semi-arid Millbrook catchment-reservoir system that supplies drinking water to north-eastern suburbs of Adelaide, South Australia. The catchment hosts viti- and horticultural land uses. The warm-monomictic, mesotrophic reservoir is artificially aerated in summer. After validating the simulation results for both Millbrook catchment and reservoir, a comprehensive scenario analysis has been conducted to reveal cascading effects of altered management practices, land uses and climate conditions on water quality in the reservoir. Results suggest that the effect on reservoir condition in summer would be severe, most likely resulting in chlorophyll-a concentrations of greater than 40 μg/l if the artificial destratification was not applied from early summer. A 50% curbing of water diversion from an external pipeline to the catchment will slightly limit chlorophyll-a concentrations by 1.22% as an effect of reduced inflow phosphate loads. The simulation of prospective land use scenarios converting 50% of present pasture in the Millbrook catchment into residential and orchards areas indicates an increase of summer chlorophyll-a concentrations by 9.5–107.9%, respectively in the reservoir. Global warming scenarios based on the high emission simulated by SWAT-SALMO did result in earlier growth of chlorophyll-a but overall the effects on water quality in the Millbrook reservoir was not significant. However scenarios combining global warming and land use changes resulted in significant eutrophication effects in the reservoir, especially in the unmanaged condition with stratification in summer. This study has demonstrated that complementary model ensembles like SWAT–SALMO allow to comprehend more realistically cascading effects of distinct catchment processes on internal reservoir's processes, and facilitate integrated management scenarios. Highlights: Process-based catchment and lake models were utilized to reveal the cumulative impacts of internal and external sources on the drinking water reservoir. Artificial destratification during summer periods provides an effective solution for algae bloom control in the reservoir meanwhile reducing external water diversion from pipelines may further decrease the inflow pollution loads and improve the water quality condition in the reservoir. Land use replacement of 50% of pasture land use by orchards indicated extreme effects on the reservoir water quality. Global warming solely did not significantly affect the water condition of the warm monomictic, mesotrophic reservoir in semi-arid climate region. Most severe impact resulted from the combined scenarios of reservoir's summer stratification, land use change and global warming.